Studi kasus asuhan keperawatan pada bayi dengan epilepsi - Nur Hijrah Tiala; Virginia Syafrinanda (THE JOURNAL OF Mother and Child Health Concerns, 2025)
Background: Epilepsy is a neurological disorder that affects people of all ages. In children, epilepsy can have a significant impact on various aspects of life, including cognitive, emotional, and social development. Infants who experience recurrent seizures are at higher risk of developmental delays as well as social and emotional problems as they grow. Purpose: To describe the application of nursing care in an infant (Baby E) with epilepsy. Method: This study employed a case study design, starting from assessment to evaluation of nursing care in Alamanda Ward, Abdoel Moelok Hospital, Lampung, in August 2025. Nursing care was provided to the patient for three days. Result: Baby E experienced three nursing problems: ineffective airway clearance, risk of ineffective cerebral perfusion, and risk of injury. The interventions were carried out for three days based on the Indonesian Nursing Intervention Standards, including observational, therapeutic, educational, and collaborative actions. Conclusion: After three days of nursing care, the problems of ineffective airway clearance and risk of injury were resolved. However, the problem of risk of ineffective cerebral perfusion was not fully resolved, indicating the need for continued monitoring and regular epilepsy therapy, as the child remains diagnosed with epilepsy.